1994
DOI: 10.1542/peds.93.2.289
|View full text |Cite
|
Sign up to set email alerts
|

Pediatrician Interview Style and Mothers' Disclosure of Psychosocial Issues

Abstract: Objective. Primary care pediatricians play an important role in the detection, diagnosis, treatment, and referral of children with mental health problems. Some parents, however, are reluctant to discuss behavioral and emotional symptoms with their child's pediatrician. Studies of patient-physician communication suggest that specific aspects of pediatrician interview style (asking questions about psychosocial issues, making supportive statements, and listening attentively) increase disclosure of sensitive infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Beyond surveys, future concern dismissal research should incorporate perspectives of providers and pediatric patients. This may include using recordings of pediatric medical encounters (Callery & Milnes, 2012;Giambra et al, 2018;Wissow et al, 1994Wissow et al, , 2005 or written vignettes (Igler et al, 2020;Lang et al, 2018), to allow for more objective study of concern dismissal. Prior vignette studies of pain dismissal experiences may also serve as models for more detailed explorations (e.g., Igler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond surveys, future concern dismissal research should incorporate perspectives of providers and pediatric patients. This may include using recordings of pediatric medical encounters (Callery & Milnes, 2012;Giambra et al, 2018;Wissow et al, 1994Wissow et al, , 2005 or written vignettes (Igler et al, 2020;Lang et al, 2018), to allow for more objective study of concern dismissal. Prior vignette studies of pain dismissal experiences may also serve as models for more detailed explorations (e.g., Igler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Again, direct questioning is most conducive to disclosure in discussing psychosocial issues with parents. 86 Parents often may not know about an adolescent's suicidal thoughts, or they may overreport concerns. 87 In a study of psychiatrically hospitalized adolescents and their parents, adolescents reported significantly more suicidal ideation, plans, and attempts than their parents.…”
mentioning
confidence: 99%
“…Results of an early study indicated that “three simple communication skills” (Wissow, Roter, & Wilson, 1994, p. 289) were related to disclosure of mental health or psychosocial issues; the authors identified these as “asking questions about psychosocial issues, making supportive statements, and listening attentively” (Wissow et al, 1994, p. 289). Wissow and colleagues (2003) have also noted the importance of “patient-centeredness,” which is congruent with these three skills and encompasses interpersonal sensitivity, partnership, and medical information giving, while others have reported a strong association between communication and parents’ perceptions of satisfaction and quality of care (Hart, Kelleher, Drotar, & Scholle, 2007).…”
mentioning
confidence: 99%